Teachers' Perceptions of Differentiated Learning in Merdeka Curriculum in Elementary Schools - Digna, Dea; Minsih; Choiriyah Widyasari (Universitas Pendidikan Ganesha, 2023)
The curriculum is dynamic, meaning it can continue to change according to the times. The Merdeka Curriculum is a curriculum that aims to optimize the talents and interests of students with character and competence. This study aimed to analyze teachers' perceptions of differentiated learning in the independent curriculum, especially at the elementary school level. This type of research is qualitative. The method used is a mixed method using questionnaires and interviews with 30 teachers. The instrument used in collecting data is a questionnaire. Research data were analyzed using data triangulation analysis. The study results show that the teacher's enthusiasm for learning the new curriculum is very high, and the participation of teachers in the independent curriculum training is also relatively high. However, this is not directly proportional to the teacher's understanding of differentiated learning. Only a few teachers already understand differentiated learning, and most must implement it in their classes. It was concluded that teachers understand the need for curriculum changes that follow community developments, so teachers are not burdened with curriculum changes.